2018
DOI: 10.1159/000487147
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features and Prognosis of Gastrointestinal Stromal Tumor Located in the Jejunum and Ileum

Abstract: Background: Data about the clinicopathological features and prognosis of gastrointestinal stromal tumors (GISTs) located in jejunum and ileum are lacking. The present study aims to investigate the features and prognosis of jejunal and ileal GISTs based on the Surveillance, Epidemiology, and End Results (SEER) database. Patients and Methods: Cases of jejunal and ileal GISTs were extracted from SEER database. Clinicopathological characteristics and survival data of patients were recorded. The clinicopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…2a, G-GIST seemed to share similar score with duodenal GIST (D-GIST), while jejunal GIST (J-GIST) patients were more likely to have LIM than ileal GIST (I-GIST) patients. Although I-GIST and J-GIST were reported to share compared prognosis in the study of Feng et al [54], we suggested that more aggressive treatment should be taken into consideration to J-GIST for the high risk of LIM. In comparison with colon GIST (C-GIST), rectal GIST (R-GIST) tended to have more positive prognosis in spite of the less likelihood of surgical resection [50], analogous result could be found in the current study.…”
Section: Discussionmentioning
confidence: 62%
“…2a, G-GIST seemed to share similar score with duodenal GIST (D-GIST), while jejunal GIST (J-GIST) patients were more likely to have LIM than ileal GIST (I-GIST) patients. Although I-GIST and J-GIST were reported to share compared prognosis in the study of Feng et al [54], we suggested that more aggressive treatment should be taken into consideration to J-GIST for the high risk of LIM. In comparison with colon GIST (C-GIST), rectal GIST (R-GIST) tended to have more positive prognosis in spite of the less likelihood of surgical resection [50], analogous result could be found in the current study.…”
Section: Discussionmentioning
confidence: 62%
“…They found rectal GISTs to be associated with improved overall survival while colonic GISTs were associated with worse overall survival [ 20 ]. On the other hand Feng et al studied small intestinal GISTs and found jejunal and ileal GISTs to be comparable in terms of prognosis [ 21 ].…”
Section: Main Textmentioning
confidence: 99%
“…2a, G-GIST seemed to share similar score with duodenal GIST (D-GIST), while jejunal GIST (J-GIST) patients were more likely to have LIM than ileal GIST (I-GIST) patients. Although I-GIST and J-GIST were reported to share compared prognosis in the study of Feng et al [49] , we suggested that more aggressive treatment should be taken into consideration to J-GIST for the high risk of LIM. In comparison with colon GIST (C-GIST), rectal GIST (R-GIST) tended to have more positive prognosis in spite of the less likelihood of surgical resection [45] , analogous result could be found in the current study.…”
Section: Discussionmentioning
confidence: 62%